Teaching Anaesthesia Residents Advanced Airway Skills:: A Proposal for Teaching Orotracheal Intubation Using a Fiberoptic Bronchoscope - Estilita, Joana Berger; Steck, Katharina (Journal of the Portuguese Society of Anesthesiology, 2019)
The correct teaching of technical skills is fundamental to ensure patient safety. According to the Practice Guidelines for Management of Difficult Airway from the ASA, an awake intubation with a flexible bronchoscope should be attempted first, whenever a difficult airway is anticipated. Therefore, trainees should be autonomous in the successful use of a fiberoptic bronchoscope when faced with difficult airway management. This paper describes an educational proposal for teaching fibreoptic intubation to trainees. Such a strategy can be used in hospitals that do resident training. A few conceptual frameworks behind this strategy will be discussed first, followed by an instructional checklist to guide the trainee in the procedure, without risking patient safety.